2019
DOI: 10.1097/md.0000000000018466
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and willingness to perform Hands-Only cardiopulmonary resuscitation among college students in Malaysia

Abstract: Worldwide, millions of people die of sudden cardiac arrest every year. This is partly due to limited and sometimes ineffective bystander cardiopulmonary resuscitation (CPR). The need for mouth-to-mouth contact, fear of causing harm, litigation, and the complexity of delivering CPR are the main deterrents. In view of this, the basic life support algorithm has been simplified and lay rescuers are encouraged to perform Hands-Only CPR. The objective of this study is to assess knowledge on and willingne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 21 publications
1
31
0
5
Order By: Relevance
“…33 Compared with other series, our cohort has lower rates of previous CPR training against developed and high-income countries (as Norway, Denmark, USA, Portugal, and Japan) 19,21,28,29,31 but is similar to those found in upper-middle, lower-middle and low-income countries (as China, Turkey, and Malaysia). 17,34 Unfortunately, to this date, Mexico has no programs to implement mandatory CPR training in the scholar curricula; we face several barriers to improve these health policies, especially their economic cost and trainer availability. 35 Although we did not find a significant difference between students' knowledge from the public and private universities, socioeconomic status is likely a key determinant of access to CPR learning and survival rates, 27,36 since many low-income students fail to reach a university education, we do not know their current status in our country.…”
Section: Wwwmedigraphicorgmxmentioning
confidence: 99%
“…33 Compared with other series, our cohort has lower rates of previous CPR training against developed and high-income countries (as Norway, Denmark, USA, Portugal, and Japan) 19,21,28,29,31 but is similar to those found in upper-middle, lower-middle and low-income countries (as China, Turkey, and Malaysia). 17,34 Unfortunately, to this date, Mexico has no programs to implement mandatory CPR training in the scholar curricula; we face several barriers to improve these health policies, especially their economic cost and trainer availability. 35 Although we did not find a significant difference between students' knowledge from the public and private universities, socioeconomic status is likely a key determinant of access to CPR learning and survival rates, 27,36 since many low-income students fail to reach a university education, we do not know their current status in our country.…”
Section: Wwwmedigraphicorgmxmentioning
confidence: 99%
“…In the study carried out by Rosell-Ortize et al [ 1 ], it was estimated that there were 20 cases per 100,000 habitants in Spain from 2013 to 2014. Despite significant advances in prevention, OHCA continues to be a major public health problem, as millions of people die from sudden cardiac arrest each year [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…They further noted the importance of BLS and ALS training being incorporated into the nursing curriculum. Baldi et al [ 8 ] analyzed the knowledge of cardiac arrest and CPR of medical students in their final year of study from all over Europe and confirmed that their knowledge of cardiac arrest and CPR upon graduating was limited and needed to be improved. Another study evaluated the effects of an online BLS course on nursing students’ learning and noted that it was an effective method for teaching and learning key BLS skills, in which students were able to accurately apply BLS techniques during CPR simulation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations